METAMORPHOSES OF THE CINEMA CLUB MOVEMENT / МЕТАМОРФОЗЫ КИНОКЛУБНОГО ДВИЖЕНИЯ ВЧЕРА И СЕГОДНЯ - RAZLOGOV KIRILL E. / РАЗЛОГОВ К.Э.; PARKHOMENKO EVGENIA V. / ПАРХОМЕНКО Е.В. (Наука телевидения, 2021)
The article is based on the studies by the Department for the Development and Approbation of Film Education Methods (VGIK) in the field of amateur film associations and cinema clubs. The authors profile the history of the Russian film club movement and analyze the significance of such associations for cultural enlightenment and comprehensive education of a personality. Such a survey is included in the international process of the formation of a cinephile community, who in the USSR were called nothing short of “kinomany” (movie addicts). A hundred years of experience of Russian film education, in the forms of both spontaneous amateur one and complex state one, is considered as a source of methods and best practices to be implemented in modern media education. The article also explains the influence of film clubs and their repertoire on the distribution and popularization of cinema works, especially on the socalled festival and “shelved” films, limited in release then and now becoming a battleground between commercial and artistic priorities of the filming process. The text contains stories and descriptions of participants in the film club movement: the founders of associations, curators and critics. Their interviews make it possible to imagine a three-dimensional picture of the life of cinema lovers’ communities. The main milestones in the history of the film club movement in the USSR and in the world are traced: the formation in the 1910s–1920s, the decline in the 1930s–1940s, the revival of the international festival movement abroad after World War II, and in Russia—during the perestroika, the crisis of the 1980s–1990s, the creation of the Cinema Club Federation, attempts to revive the Friends of Soviet Cinema Society, and modern trends related to the film club work in the context of international cooperation, which was initiated by the VI World Festival of Youth and Students. The Soviet experience is studied in correlation not only with the strengthening in Western Europe of such phenomena as film clubs and film lovers’ associations, but also with the formation of specialized art cinemas and the experiment of the cinema club network, which is predicted to play a special role in the postpandemic era. Among other things, the authors’ attention is focused on the delicate balance, that accompanied the entire history of the film club movement: the balance between initiative of the people, a spontaneous mass movement, and state efforts to organize and structure this process, between the desire for creative freedom and strict censorship of the elite. The authors consider the domestic and foreign cinema club experience as an opportunity to distribute works of the Russian cinema art among the most interested audience and to establish a system of limited cinema club distribution, which would bring originators and the public closer together.